The Problem of Autonomy in Modem Education and Self –Development - Bulajeva, Tatjana (Acta Paedagogica Vilnensia, 2002)
For long centuries the problem of autonomy in education was not discussed, because of the prevailing concept existing at the time. The learners were understood as the homogeneous group children or young people and their learning was understood as the process being controlled by the teacher, who had all the responsibility for the knowledge that pupils had to acquire and the progress that they had to make in learning and personal development. From the modem perspective - autonomy is understood as the most important aspect of the system of development and self-development of man, as the authorship of life. This article focuses on the problem of conceptualizing the autonomy in educational theory. It presents some peculiarities of autonomy in education, typology of autonomy, defining structural and functional autonomy, absolute and relative autonomy. The personal autonomy is understood as an important condition for conducting competent self-development as well as the aim of self-development. The article also dwells on the problems of autonomy and heteronomy of adult learners (teachers), involved in personal and professional self-development. To organize a competent self-development and professional development an adult learner has to be an autonomous person so as to be able to control one's life, professional career and personal learning.
Keywords: Andragogy; education; self –development; autonomy; typology of autonomy.